2017
DOI: 10.1021/acs.energyfuels.7b00863
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Fluid Viscosities on the Rate of Countercurrent Spontaneous Imbibition

Abstract: An analysis of the fundamental equation for countercurrent spontaneous imbibition (SI) for water-wet porous media has been performed based on a generalized mobility term MTGEN accounting for fluid–solid and fluid–fluid interaction developed by Andersen et al. (10.3997/2214-4609.201700303IOR 201719th European Symposium on Improved Oil RecoveryEuropean Association of Geoscientists & Engineers (EAGE)Houten, The Netherlands2017). MTGEN contains an additional term in the denominator, compared to the standard mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…66,83,96 The latest model is shown in eq 30. 66 It accounts for the effect of end points of relative permeability functions, the curvature of the relative permeability curves, and a fluid−fluid interaction that considers the viscous coupling effects. Therefore, it, in principle, is universally valid for co-current imbibition, all fluid viscosities, and all relative permeability shapes where k rwe and k rnwe are the relative permeabilities of the wetting and non-wetting phases at the end point, respectively, α and β are the saturation exponents of the wetting and nonwetting phases, respectively, which are related to the Coreytype expression, 97 S w * is a characteristic saturation of the wetting phase, which is usually equal to 0.5, and I is a fluid− fluid interaction coefficient.…”
Section: Handy's Model For Imbibition In Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…66,83,96 The latest model is shown in eq 30. 66 It accounts for the effect of end points of relative permeability functions, the curvature of the relative permeability curves, and a fluid−fluid interaction that considers the viscous coupling effects. Therefore, it, in principle, is universally valid for co-current imbibition, all fluid viscosities, and all relative permeability shapes where k rwe and k rnwe are the relative permeabilities of the wetting and non-wetting phases at the end point, respectively, α and β are the saturation exponents of the wetting and nonwetting phases, respectively, which are related to the Coreytype expression, 97 S w * is a characteristic saturation of the wetting phase, which is usually equal to 0.5, and I is a fluid− fluid interaction coefficient.…”
Section: Handy's Model For Imbibition In Rocksmentioning
confidence: 99%
“…When eqs , , , , , and are combined, then eq can be written as follows: The conservation equation of the wetting phase (displacing phase) is written as follows: , where S is the saturation.…”
Section: Mechanisms Of Eor By Imbibitionmentioning
confidence: 99%
“…So-called COUC relative permeabilities is a concept introduced to account for the observed lower fractional recovery rate in COUC SI tests compared to cocurrent SI tests. The physical argument for introducing COUC relative permeability curves is based on that momentum transfer between two immiscible fluids is dependent on whether the fluids are moving co- or counter currently. , Since the magnitude and impact this effect may have on the individual water and oil relative permeability curves, the concept of COUC relative permeabilities adds uncertainty when such processes are simulated. The choice used by Bourbiaux and Kalaydjian was to reduce the measured water and oil cocurrent relative permeability curves with the same factor (= 0.7) when used to simulate COUC processes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The physical argument for introducing COUC relative permeability curves is based on that momentum transfer between two immiscible fluids is dependent on whether the fluids are moving co-or counter currently. 58,59 Since the magnitude and impact this effect may have on the individual water and oil relative permeability curves, the concept of COUC relative permeabilities adds uncertainty when such processes are simulated.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been observed that inclusion of the fluid-fluid interaction termk ow (u w − u o ) can give improvements over standard Darcy's equation based formulation for water-oil flow in porous media. We refer to [35,31] for a first discussion of this in the context of core scale modelling and generalized permeability functions and [36] for a discussion of this generalized two-phase flow in the context of imbibition (i.e., capillary pressure driven counter-current flow). • The viscous terms ε o ∇ · (n∇u o ) and ε w ∇ · (m∇u w ) in (1.1) 3,4 can account for frictional forces within the fluid due to its viscosity.…”
Section: (Communicated By Paola Goatin)mentioning
confidence: 99%